Expression of Cyclooxygenase Enhances Tumor Invasion and Metastasis in Human Gastric Carcinoma - Murdani Abdullah; Abdul Aziz Rani; Daldiyono Hardjodisastro; Hiroyuki Otsuka; Tadashi Sato; Yuichiro Kojima; Masayuki A Fujino (The Indonesian Society for Digestive Endoscopy, 2004)
Background: Expression of COX-2 in vitro has been shown to have a number of cellular effects including increasing proliferation, reducing apoptosis promoting angiogenesis, decreasing E-cadherin expression and increasing invasive/metastatic potential. Aims: To determine the role of COX-2 in the development and metastasis potential of gastric carcinoma in human subjects. Methods: Tissue samples were obtained from surgically removed specimens of 48 patients with primary gastric adenocarcinoma who underwent gastrectomy from January 1998 to December 1999. The specimens were stained for HE while COX-2 expressions in cancer fold and antrum site were evaluated immunohistochemically. Expression of COX-2 was defined as positive when either one of cancer lesion or antrum site showed immunoreactivity. Results: Preliminary result from 12 out of 48 cases, COX-2 immunoreactivity was detected in 50% (6 of 12 specimens). Expression of COX-2 were more frequent in tumor with serosal invasion (5 of 6 specimens), lymph node metastases (3 of 3 specimens), tumor size more than 4 cm and were significant, statistically (p0.05). The expression of COX-2 in well differential carcinoma type was similar with in poorly differentiated carcinoma type. Conclusion: COX-2 expression in gastric carcinoma tissue is correlated closely with tumor size, serosal invasion and lymph node metastases, indicating that COX-2 is involved in the growth and metastases of gastric carcinoma. Keywords: Gastric carcinoma, cyclooxygenase-2, invasion, immunochemistry